Amine-Salt-Assisted Solution Crystallization of Inorganic Perovskite Single Crystals for High-Performance X-Ray Detection - Jiang, Yujia; Chu, Depeng; Pi, Jiacheng; Liu, Naiming; Sun, Xueni; Zhang, Yunxia; Feng, Ziyang; Wang, Yuquan; Chen, Wenjie; Wang, Xinxin; Tian, Jingyun; Zhao, Lei; et al. (Nano-Micro Letters, 2026)
Inorganic perovskite CsPbCl3 single crystals (SCs) are promising for stable and high-performance X-ray detection due to their high X-ray absorption, superior optoelectronic properties, and superior chemical and thermal stability. However, the size of CsPbCl3 SCs grown via low-energy-consumption solution methods remains limited to below 1 mm, primarily because of the limited solubility of raw materials in solvents and the lack of effective growth techniques. In this work, an amine-salt-assisted solution crystallization strategy is developed to grow high-quality CsPbCl3 SCs with size up to 15 mm. This significant size improvement is enabled by a 13-fold increase in precursor solubility, achieved by constructing hydrogen bond interactions between the amine salt and insoluble raw materials. Consequently, the SCs exhibit high μτ product (6.3 × 10–3 cm2 V−1), low trap density (2.9 × 1010 cm−3), and large resistivity (1.7 × 109 Ω cm). Therefore, the SC detectors achieve a record-high sensitivity of 76,624 μC Gy−1 cm−2 and a low detection limit of 47.9 nGy s−1 even under low bias voltages, enabling high contrast X-ray imaging. This ingenious and executable low-temperature solution crystallization strategy combined with superior X-ray detection performance makes CsPbCl3 SCs promising to advance the low-cost development of safe radiation detection systems. Highlights: 1 An amine-salt-assisted solution crystallization strategy is developed to grow high-quality CsPbCl3 single crystals (SCs) with a size as large as 15 mm, the SCs exhibit a high carrier mobility-lifetime product, low trap density, and large resistivity. 2 The CsPbCl3 SC X-ray detector achieved a high detection sensitivity of 76,624 μC Gy-1 cm-2 and a low detection limit of 47.9 nGy s-1, a short response time of 700 μs, therefore realized high contrast X-ray imaging.